The Invisibility of the Asian American Identity in North American Bioethics - Huerne, Katherine (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2023)
This Perspective sheds light on the major barriers behind Asian American invisibility in bioethics, such as the inconsistencies in defining a coherent identity in North American society, the systemic mechanisms of invisibility from history to healthcare based on immigration status, and scarcity of bioethics literature about their perspectives. The consequences of Asian American invisibility in bioethics and healthcare practises are also discussed, including a reflection of the interconnected mechanisms between academic bioethical theory and healthcare practises that perpetuate Asian American invisibility. Finally, recommendations are provided to begin a critical reflection of bioethical theory with Asian Americans in mind. This serves as the stepping-stone for future discussions on Asian American bioethics, to highlight a missing perspective in North American race-based activism regarding the equity, diversity, and inclusion of an underrepresented demographic.